Molecular analysis of terminalia spp. distributed in Thailand and authentication of crude drugs from terminalia plants - Aekkhaluck Intharuksa (2018)
© 2016 The Pharmaceutical Society of Japan. Terminalia, a large genus of Combretaceae, is distributed in Tropical Asia, Africa, and America. Some Terminalia plants are used in folk medicine because they possess powerful medicinal properties. Dried fruits of Terminalia bellirica and Terminalia chebula are used as the main ingredient in Triphala, a famous polyherbal formulation in Ayurvedic medicine and Thai folk medicine, because of their laxative, detoxifying, and rejuvenating effects. To clarify the phylogenetic relationships of medicinal Terminalia species (T. bellirica, T. chebula, and T. catappa) and authenticate their crude drugs, "Samo" and Triphala, nucleotide sequencing alignments in the internal transcribed spacer one-two (ITS 1-2) regions of Terminalia plants collected in Thailand were performed. The amplified fragments of Terminalia species were approximately 800 bp in length. To compare these sequences and DDBJ registered data, a molecular phylogenetic tree was constructed. Phylogenetic analysis clearly separated the sequences into two groups: Asian Terminalia and African Terminalia with some exceptions. In the analyzed sequences, the length of the ITS1-5.8S-ITS2 region was 674 bp in T. chebula, and 677 bp in T. bellirica and T. catappa. Eighty-one single nucleotide polymorphisms (SNPs) and nine insertion-deletions (indels) were observed, and the nucleotide sequences of this region showed species-specific sequences. Based on these differences, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and amplification refractory mutation system (ARMS) were applied to identify medicinal Terminalia species. Moreover, the ARMS method was chosen for fingerprinting analysis of Samo crude drugs and Triphala formulations because it was a fast, cost-effective, and reproducible approach.